Spatio‐Temporal Variations in Water Quality of Muttukadu Backwaters, Tamilnadu, India. (1st July 2013) - Srinivasan, Kalpana; Natesan, Usha
ABSTRACT: : Muttukadu Backwater, located on the east coast of Tamilnadu, is one of healthiest estuarine environments in the region. A study pertaining to seasonal variations in physico‐chemical properties in water was conducted at nine sites of Muttukadu Backwater for a period of one year (January to December 2009). Multivariate statistical techniques, such as cluster analysis and principal component analysis (PCA), were applied to evaluate the variation in water quality of Muttukadu Backwater and to identify pollution sources. In order to analyze water quality, a geographic information systems (GIS) software package, Arc GIS version 9.3, was used (Esri, Redlands, California). An interpolation technique, inverse distance weighting, was used to produce the spatial distribution of water quality parameters over the backwater. The purpose of the technique was to aid in protection of the environment and ecology of the estuary and aid in effective management. In the present study, observed values of salinity, nitrite, nitrate, ammonia, total nitrogen, phosphate, and silicate were significantly high in the estuarine zone. PCA resulted in three factors explaining 75.9% of the total variance. Principal component 1 exhibited a high correlation with significant physico‐chemical variables representing the influence of tidal action and sandbar formation. Principal component 2 represented natural pollution as a result of surface runoff. Principal component 3 represented natural pollution as a result of nutrient pollution.